ANALYSIS OF NURSE'S EFFORTS TO CONTROL NOSOCOMIAL INFECTIONS IN THE COVID-19 PANDEMIC PERIOD IN HOSPITAL - Rafi'ah, Rafi'ah; Hariyanto, David (Jurnal Keperawatan Respati Yogyakarta, 2021)
Nosocomial infection is an infection acquired from the hospital. The risk of nosocomial disease can occur in addition to patients treated in the hospital. It can also happen in hospital staff, including nurses. The purpose of this study was to identify respondent characteristics and analyze the relationship between the knowledge and skills of nurses on efforts to control the Nosocomial infection chain during the Covid-19 pandemic. This research is quantitative research with observational analytic and using a cross-sectional research design. The sampling technique used in this study was cluster random sampling with a sample size of 51 respondents. Data analysis in this study used the SPSS test with Spearman Rank analysis. This study indicated that the majority of respondents are in the age range between 20-30 years, as many as 34 respondents (66.7%). The majority of them are female, as many as 35 respondents (68.6%). Most respondents were a Bachelor's degree, as many as 26 respondents (51,0%). Lastly, most respondents had a service period of > 5 years, as many as 25 respondents (49.0%). The results of the Spearman Rank analysis show that the p-value is 0.015, which means less than < 0.05, which means that there is a significant relationship between knowledge and skills of nurses in nosocomial infection chain control efforts during the Pandemic Covid-19. Therefore, apart from providing personal protective equipment (PPE), hospital management must educate health workers, especially nurses, about controlling the chain of nosocomial infections and Covid-19. Keywords: Nosocomial Infection; Nurse; Knowledge; Skills